2019
DOI: 10.1002/ece3.5851
|View full text |Cite
|
Sign up to set email alerts
|

Altitude shapes the environmental drivers of large‐scale variation in abundance of a widespread mammal species

Abstract: Aim: Habitat quality and heterogeneity directly influence the distribution and abundance of organisms at different spatial scales. Determining the main environmental factors driving the variation in species abundance is crucial to understand the underlying ecological processes, and this is especially important for widely distributed species living in contrasting environments. However, the responses to environmental variation are usually described at relatively small spatial scales. Here, we studied the variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…The evenness, diversity, abundance, and taxa richness of butterflies in each habitat in Lumajang is different (Figure 3). The differences are because butterflies' activity, growth, reproduction, and even distribution depend on environmental factors (Jacquier et al 2020;Koneri et al 2022). The Community Forest was the habitat with the most butterfly species than other study sites.…”
Section: Discussionmentioning
confidence: 89%
“…The evenness, diversity, abundance, and taxa richness of butterflies in each habitat in Lumajang is different (Figure 3). The differences are because butterflies' activity, growth, reproduction, and even distribution depend on environmental factors (Jacquier et al 2020;Koneri et al 2022). The Community Forest was the habitat with the most butterfly species than other study sites.…”
Section: Discussionmentioning
confidence: 89%
“…Altitude is one of the major environmental factors that affects the survival of organisms, and organisms evolve specific phenotypic survival traits in response to their environment [ 1 ]. Tibetan sheep bred on the Qinghai–Tibet Plateau, one of the oldest sheep breeds and one of the three major sheep breeds with coarse wool in China, are naturally raised throughout the year.…”
Section: Introductionmentioning
confidence: 99%
“…Food availability is an important environmental variable in ecological studies in birds [ 13 ], reptiles [ 14 ], and mammals [ 15 , 16 ]. Studies suggested that food availability plays a key role in determining home range size in many primates [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%